An Active State of Charge Balancing Method With LC Energy Storage for Series Battery Pack - Xu, Xiaozhuo; Xing, Cheng; Wu, Qi; Qian, Wei; Zhao, Yunji; Guo, Xiangwei (Frontiers in Energy Research, 2022)
To reduce the impact of series battery pack inconsistency on energy utilization, an active state of charge (SOC) balancing method based on an inductor and capacitor is proposed. Only one inductor and one capacitor can achieve a direct transfer of balanced energy between the highest power cell and the lowest power cell. This method has the characteristics of a simple structure, small size, simple control, fast balancing speed, and low topology cost. First, the topology, working principle, parameter design, and control strategy of the proposed balancing method are explained. Second, the characteristics of the speed and efficiency are analyzed through the simulation models, and the advantages of its low topology cost and simple control are explained. Finally, by building an experimental platform for a four-cell series battery pack, the effectiveness of the new balancing method in the charging/discharging process and the dynamic process of the battery pack is verified. After the end of the balancing, the SOC difference is less than 4%.